Quantification of heterogeneity in human CD8+ T cell responses to vaccine antigens: an HLA-guided perspective - Harris, Duane C.; Shanker, Apoorv; Montoya, Makaela M.; Llewellyn, Trent R.; Matuszak, Anna R.; Lohar, Aditi; Kubicek-Sutherland, Jessica Z.; Li, Ying Wai; Wilding, Kristen; Mcmahon, Ben; Gnanakaran, Sandrasegaram; Ribeiro, Ruy M.; et al. (Frontiers in Immunology, 2024)
Vaccines have historically played a pivotal role in controlling epidemics. Effective vaccines for viruses causing significant human disease, e.g., Ebola, Lassa fever, or Crimean Congo hemorrhagic fever virus, would be invaluable to public health strategies and counter-measure development missions. Here, we propose coverage metrics to quantify vaccine-induced CD8+ T cell-mediated immune protection, as well as metrics to characterize immuno-dominant epitopes, in light of human genetic heterogeneity and viral evolution. Proof-of-principle of our approach and methods are demonstrated for Ebola virus, SARS-CoV-2, and Burkholderia pseudomallei (vaccine) proteins.